Public and Private-Led Urban Developments in Post-colonial Zimbabwe: a Comparative Study in Ruwa Town - Muzorewa, Terence Tapiwa (Springer, 2021)
This article compares private-led development with public-led development within the private-public partnership approach framework in the growth process of Ruwa Town in Zimbabwe. The comparison gives insights into the best alternatives to post-colonial urban development in Zimbabwe in general and Ruwa Town in particular at a time when the government of Zimbabwe is contemplating adopting the private-public partnership approach to urban development. Ruwa has been involved in a transition in urban development approach, from public-led development to private-led development. The town is outstanding for involving private land developer companies (PLDCs) in developing its urban infrastructure. The companies were invited by the public sector to create a partnership in service provision and infrastructure development. Upon entering the land market in Ruwa, from 1987, the companies bought land from commercial farmers around the town which they developed into residential, commercial and industrial areas before selling it to individuals and other entrepreneurs. Public-led development in Ruwa was driven by the Government and the Ruwa Town local authorities, and these public entities developed their own industrial areas and residential parks. In comparing private- and public-led developments, the article uses qualitative research methods to derive research data. The comparison proves that the companies were more effective in providing quality infrastructure. Although the companies had some shortcomings which retarded growth in the area, the article argues that they were the most appropriate vehicles of transformation in Zimbabwe’s urban development process from a public-led approach to a neo-liberal approach.